DAMPAK KEMITRAAN USAHA PETERNAKAN AYAM RAS PEDAGING TERHADAP BIAYA PRODUKSI DAN PENDAPATAN DI KOTA METRO - Novi Rosanti; Nia Okta Sari; Teguh Endaryanto (Journal of Integrated Agribusiness, 2022)
Partnership pattern was the pattern of managing broiler chicken business through cooperation with companies that offered many benefits so that most breeders were encouraged to established partnership patterns. But in the implementation of partnerships not always run in accordance with the agreement because there were some frauds committed by farmers and companies. The risk of frauds made some farmers chose to manage the broiler breed chicken business independently. The difference in implementation between partnership patterns and self-sustaining patterns can have a performance impact on broiler chicken breeders. This study aims to analyze the partnership patterns, analyze the partnership's driving factors and analyze the impact of partnerships on the production and income costs of broiler breed chicken farmers in Metro City. This study was conducted from October 12 to November 30, 2020 located in Metro City. The methods were used in this research were qualitative and quantitative combined methods. The data was collected through a survey by interviewing directly 59 respondents. The result of this research were The pattern of partnerships of broiler breed chicken farmers in Metro City was the plasma core pattern, 2) The driving factors of partnership in broiler chicken breeders were capital availability motivation, market guarantee motivation, price guarantee motivation and high income motivation, 3) Statistically the partnership pattern had an impact on income and labor allocation. The company could improve the services that were felt by farmer tobe lacking, such as the accuracy of providing production facillities and payment of harverts and could provide competitive sell prices to breeders partner.